Pengembangan Media Permainan Monopoli Berbasis STAD (Student Teams Achievement Division) Pada Pelajaran PKN Materi Pancasila Di Kelas VI MI R. Khufadz - Sulis Handayani (LPPM IAIN Sorong, 2025)
The objective of this research is to develop STAD-based monopoly game media for Pancasila material in Civics Education learning at MI R. Khufadz for grade VI students. Research and Development (R&D) is the type of research employed using the ADDIE development model. This study involved 17 sixth-grade students at MI R. Khufadz in Sorong Regency. Questionnaires, documentation, observation, as well as pre-test and post-test were the data collection methods. The research results indicate that the material expert validation sheet obtained a score of 40% (categorized as